2003
DOI: 10.1086/367611
|View full text |Cite
|
Sign up to set email alerts
|

Injection of Magnetic Energy and Magnetic Helicity into the Solar Atmosphere by an Emerging Magnetic Flux Tube

Abstract: We present a detailed investigation of the dynamical behavior of emerging magnetic flux using 3-dimensional MHD numerical simulation. A magnetic flux tube with a lefthanded twist, initially placed below the photosphere, emerges into the solar atmosphere. This leads to a dynamical expansion of emerging field lines as well as an injection of magnetic energy and magnetic helicity into the atmosphere. The field-aligned distributions of forces and plasma flows show that emerging field lines can be classified as eit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
125
0
2

Year Published

2006
2006
2018
2018

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 155 publications
(141 citation statements)
references
References 30 publications
14
125
0
2
Order By: Relevance
“…The twisted or sheared emerging flux may carry enough magnetic free energy, some of them may be released during the flare, and the rest may contribute to the increase of the local shear. Recent three-dimensional MHD simulations ( Fan 2001;Magara & Longcope 2001, 2003Magara 2004;Manchester et al 2004) have modeled the emergence of a twisted magnetic flux tube from solar convection zone through photosphere and chromosphere into the corona. In these simulations, a twisted flux tube is initially placed in the convection zone at a depth of about a few times the photospheric pressure scale height and the central segment of the twisted tube rises buoyantly toward the photosphere (Fan 2004).…”
Section: Summary and Discussionmentioning
confidence: 99%
“…The twisted or sheared emerging flux may carry enough magnetic free energy, some of them may be released during the flare, and the rest may contribute to the increase of the local shear. Recent three-dimensional MHD simulations ( Fan 2001;Magara & Longcope 2001, 2003Magara 2004;Manchester et al 2004) have modeled the emergence of a twisted magnetic flux tube from solar convection zone through photosphere and chromosphere into the corona. In these simulations, a twisted flux tube is initially placed in the convection zone at a depth of about a few times the photospheric pressure scale height and the central segment of the twisted tube rises buoyantly toward the photosphere (Fan 2004).…”
Section: Summary and Discussionmentioning
confidence: 99%
“…From observed line asymmetries it is concluded that the flow is located in the deep photosphere (Maltby, 1964;Schlichenmaier, Bellot Rubio, and Tritschler, 2004). …”
Section: Evershed Flowmentioning
confidence: 93%
“…The resulting estimate is thus a mixture of the enhancement of the helicity content by shearing motions and the portion of helicity emerging from below the photosphere. Magara and Longcope (2003) proposed that the helicity contribution from the vertical flows might only dominate early phases of flux emergence, followed by a dominant contribution from the shearing flows in the later stages of an evolving AR. This is in the opposite of what has been presented recently by who analyzed the ARs during their emergence phases and found that shearing motions contribute the most to the ARs' helicity content.…”
Section: Helicity Buildup and Storagementioning
confidence: 99%